2014
DOI: 10.1007/s00381-014-2496-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of CSF leak following spinal surgery

Abstract: Primary and meticulous dural closure is sine qua non in preventing postoperative CSF leak. A lumbar drain is a convenient and economical method of managing the problem initially failing which more invasive methods like re-exploration may be employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The use of a PEG-hydrogel was evaluated in another study, which reported a 5.4% CSF leak risk in procedures in which this type of sealant was used [7]. Two studies investigating the association between the use of fibrin glue and CSF leakage did not find a statistically significant effect [5,9]. Currently, we believe that there is insufficient evidence to recommend the use of additional methods to augment dural closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a PEG-hydrogel was evaluated in another study, which reported a 5.4% CSF leak risk in procedures in which this type of sealant was used [7]. Two studies investigating the association between the use of fibrin glue and CSF leakage did not find a statistically significant effect [5,9]. Currently, we believe that there is insufficient evidence to recommend the use of additional methods to augment dural closure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the current study, we will define CSF leakage as incisional CSF leakage and consider PMC separately. Furthermore, reports on CSF leakage after intradural spinal surgery based on recent data are limited and mostly include a specific indication only [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The common postoperative complications of untethering include cerebrospinal fluid (CSF) leakage, wound infection, meningitis, bladder dysfunction, and neurological deterioration [314]. We encountered complications in seven patients, in which CSF leakage occurred in four patients, two patients had worsened urinary control, and postoperative infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, postoperative CSF leakage is a known complication of spinal surgery. The ideal material to be used in the dural closure is still a matter of debate [43]. Prompt surgery is recommended to prevent the complications such as meningitis, CSF fistulas, and pseudocyst formation with potential nerve compression [44].…”
Section: Spinal Cordmentioning
confidence: 99%
“…Thus, in a retrospective analysis done by Balasubramaniam et al [43], evaluating children submitted to surgery for various spinal pathologies, FS had no effect, though the numbers were statistically too small. Jankowitz et al [55] reached a similar conclusion that the use of FS did not significantly decrease the incidence of subsequent CSF leakage while studying the potential efficacy of FS TISSEEL® (Baxter) for enhancing dural repair after lumbar spine surgery.…”
Section: Spinal Cordmentioning
confidence: 99%